Hypoxia-Inducible Factor-1α Activity as a Switch for Glioblastoma Responsiveness to Temozolomide - Lo Dico, Alessia; Martelli, Cristina; Diceglie, Cecilia; Lucignani, Giovanni; Ottobrini, Luisa (Frontiers in Oncology, 2018)
Rationale: A common driver of several pathways involved in glioblastoma (GBM) aggressiveness has been recognized in the activity of HIF-1α transcription factor whose reduction, soon after TMZ administration, has been furtherly proposed as an early response biomarker in GBM models. Since HIF-1α is a tightly regulated protein, the study of mechanisms involved in its down-regulation could shed new light to explain the mechanisms underpinning GBM sensitivity or resistance to TMZ. Methods: The influence of HIF-1α silencing in cell responsiveness to TMZ has been assessed in four genetically different human GBM cell lines by evaluating cell viability and apoptosis-related gene balance analysis. LAMP-2A silencing has been used to evaluate Chaperone-Mediated Autophagy contribution to HIF-1α activity modulation in TMZ sensitive and resistant cells. Results: Our results show that HIF-1α, and not HIF-2α activity, is associated to GBM responsiveness to TMZ. We demonstrate, moreover, that HIF-1α activity down-regulation improve glioma response to TMZ in resistant cells. At the same time, the blockage of CMA-mediated HIF-1α degradation induces resistance to TMZ in sensitive cells. These results are in line with the modulation of crucial apoptosis-related genes. Conclusion: In conclusion, we here demonstrate the central role played by HIF-1α activity in determining GBM sensitivity or resistance to TMZ and we propose CMA as the cellular mechanism responsible for its modulation in this treatment regimen.